2024
DOI: 10.1002/ajmg.b.32980
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization analysis using GWAS and eQTL data to investigate the relationship between chronotype and neuropsychiatric disorders and their molecular basis

Shane Crinion,
Cathy A. Wyse,
Gary Donohoe
et al.

Abstract: Chronotype is a proxy sleep measure that has been associated with neuropsychiatric disorders. By investigating how chronotype influences risk for neuropsychiatric disorders and vice versa, we may identify modifiable risk factors for each phenotype. Here we used Mendelian randomization (MR), to explore causal effects by (1) studying the causal relationships between neuropsychiatric disorders and chronotype and (2) characterizing the genetic components of these phenotypes. Firstly, we investigated if a causal ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Using participants from the UK Biobank, genome-wide association analyses revealed that evening chronotype is positively correlated to increased SZ risk while morning chronotype is negatively correlated to SZ (Jones et al, 2016;Jones et al, 2019;Lane et al, 2016). Additionally, mendelian randomisation analyses revealed a causal effect of chronotype on SZ and ASD (Crinion et al, 2024;Sun et al, 2022). Studies using experience sampling methodology (ESM), a technique used to capture interdaily and intradaily variations of a behaviour of interest based on a daily diary, primarily looked at the predictive power of sleep disturbances on psychotic symptoms such as paranoia (Hennig & Lincoln, 2018;Mulligan et al, 2016;Waters et al, 2011).…”
Section: Circadian Disruption As a Predictor Of Symptomsmentioning
confidence: 99%
“…Using participants from the UK Biobank, genome-wide association analyses revealed that evening chronotype is positively correlated to increased SZ risk while morning chronotype is negatively correlated to SZ (Jones et al, 2016;Jones et al, 2019;Lane et al, 2016). Additionally, mendelian randomisation analyses revealed a causal effect of chronotype on SZ and ASD (Crinion et al, 2024;Sun et al, 2022). Studies using experience sampling methodology (ESM), a technique used to capture interdaily and intradaily variations of a behaviour of interest based on a daily diary, primarily looked at the predictive power of sleep disturbances on psychotic symptoms such as paranoia (Hennig & Lincoln, 2018;Mulligan et al, 2016;Waters et al, 2011).…”
Section: Circadian Disruption As a Predictor Of Symptomsmentioning
confidence: 99%